2021
DOI: 10.1016/j.psj.2021.101510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between different breeds of laying hens in terms of eggshell translucency and its distribution in various ends of the eggshell

Abstract: Eggshell translucency is a ubiquitous external eggshell quality problem caused by variations of eggshell ultrastructure or shell membrane. In previous studies, researchers have widely investigated this phenomenon with nutritional, environmental, and genetic perspectives in many breeds. However, most studies referring to phenotypic measurement of shell translucency have been performed using a relatively subjective two-, three-, or four-grading methods, which made it impossible to compare distribution of shell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In recent years, much research has been conducted on eggshell translucency, especially with respect to the characteristics, incidence, influencing factors, and impact of this abnormality on table eggs ( Leach and Gross, 1983 ; Chousalkar et al, 2010 ; Wang et al, 2017 ; Wang et al, 2019 ; Wong et al, 2020 ; Zhang et al, 2021 ; Ren et al, 2023 ). However, despite the belief that eggshell translucency can affect incubation and hatching parameters, concrete data are scarce ( Galindo et al, 2022 ; van den Brand et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, much research has been conducted on eggshell translucency, especially with respect to the characteristics, incidence, influencing factors, and impact of this abnormality on table eggs ( Leach and Gross, 1983 ; Chousalkar et al, 2010 ; Wang et al, 2017 ; Wang et al, 2019 ; Wong et al, 2020 ; Zhang et al, 2021 ; Ren et al, 2023 ). However, despite the belief that eggshell translucency can affect incubation and hatching parameters, concrete data are scarce ( Galindo et al, 2022 ; van den Brand et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the latter study, flocks of >65 wk of age showed comparable translucency scores than the younger flocks. Baker and Curtis (1957) and Zhang et al. (2021) showed that egg translucency differed between white leghorn strains and Baker and Curtis (1957) showed that egg translucency largely varied between individual hens, and eggs of the same hen showed less variability in translucency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al. (2017 , 2019a ) and Zhang et al. (2021) investigated effects of egg translucency in relationship to other egg characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Traits of shell translucency are partly regulated by genetic factors, manifesting in differences in the severity of shell translucency among strains and between individuals. Furthermore, hens have laid eggs with the same level of translucency on consecutive days ( 3 , 6 ). In previous studies, the heritabilities of eggshell translucency were estimated to be 0.18–0.22 in 63-wk-old Brown-Egg Dwarf Layers and a 52-wk-old F 2 resource population generated from a cross between Dongxiang Blue-shelled and White Leghorn hens ( 2 ).…”
Section: Introductionmentioning
confidence: 99%